The Influence of Leadership Style on Employee Performance with Penalties as Moderating Variables - Rahayaan, Fifi Farizsa; Irawati, Sandra; Roz, Kenny (Universitas Muhammadiyah Malang, 2023)
This study aims to describe leadership style, employee performance, and punishment as moderating variables at PT. Madu Nusantara. this research is quantitative. Quantitative analysis to describe the results of the questionnaire that has been obtained from all respondents in the form of numbers. The sample used in this study was marketing employees at PT. Madu Nusantara. The sample used in this study amounted to 50 respondents. Data collection techniques using a questionnaire. The data analysis technique used is Partial Least Square.. Data processing in this study uses the SmartPLS software program. The results showed that leadership style had a positive and significant effect on the performance of employees at PT. Madu Nusantara. Punishment has a positive and significant effect on the performance of employees of PT. Madu Nusantara. Meanwhile, the influence of leadership style on employee performance with punishment as a moderating variable shows insignificant results.